Погребение начала VIII в. у села Октябрьское в Северо-Восточном Приазовье - Комар, А.В. (Інститут археології НАН України, 2006)
The paper presents the female burial 7 of barrow VI near Oktyabrskoie village of Novoazovsk region of Donetsk province. The burial was made in a simple pit of a sub-oval shape and oriented to the west with deviation to the south. It contained a horse skull and extremities, a knife and scissors, bronze buttons and “heraldic”style buckle. Having the same rite as Oguze burials of the IX-X c. this burial, nevertheless, is dated to much earlier time (the beginning of the VIII c.) which permits to link it to the group of similar burials from Zaplavka and Krylovka in the Northern Black Sea Littoral. It is quite possible that the similarity of funeral rites of these burials to Oguze ones is not casual, and the migration of Khazars in the Northern Black Sea Littoral at the end of the VII c. also involved a part of Oguzes related with them. Which resulted in a burial from Oktyabrskoie in Azov reaches.